Chewing gum to treat postoperative nausea and emesis in female patients (CHEWY): rationale and design for a multicentre randomised trial. Issue 6 (12th June 2019) - Darvall, Jai; von Ungern-Sternberg, Britta Sylvia; Braat, Sabine; Story, David; Davidson, Andrew; Allen, Megan; Tran-Duy, An; Middleton, Dana; Leslie, Kate
Abstract : Introduction: Postoperative nausea, retching and vomiting (PONV) remains one of the most common side effects of general anaesthesia, contributing significantly to patient dissatisfaction, cost and complications. Chewing gum has potential as a novel, drug-free alternative treatment. We aim to conduct a large, definitive randomised controlled trial of the efficacy and safety of peppermint-flavoured chewing gum to treat PONV in the postanaesthesia care unit (PACU). If chewing gum is shown to be as effective as ondansetron, this trial has the potential to significantly improve outcomes for tens of millions of surgical patients around the world each year. Methods and analysis: This is a prospective, multicentre, randomised controlled non-inferiority trial. 272 female patients aged ≥12 years having volatile anaesthetic-based general anaesthesia for breast or laparoscopic surgery will be randomised. Patients experiencing nausea, retching or vomiting in PACU will be randomised to 15 min of chewing gum or 4 mg intravenous ondansetron. The primary outcome (complete response) is cessation of PONV within 2 hours of administration, with no recurrence nor rescue medication requirement for 2 hours after administration. Ethics and dissemination: The Chewy Trial has been approved by the Human Research Ethics Committees at all sites. Dissemination will be via international and national anaesthesia conferences, and publication in the peer-reviewed literature. Trial registration number: ACTRN12618000429257; Pre-results.